New opportunities for using transdermal forms of estradiol in ART programs - V.V. Kotlik; M.I. Grytsko (Publishing House TRILIST, 2021)
Objective of this review is to summarize the accumulated data on the use of estradiol transdermal gel in the form of a bottle with a pump-dispenser Oestrogel® in the treatment of "thin" endometrium and in assisted reproductive technologies (ART) programs. "Thin" is the endometrium with thickness on ultrasound not exceeds 7 mm during ovulation and is characterized by complete or partial absence of conditions for ovum implantation. Endometrial thickness of 8 mm is referred to as hypoplastic endometriopathy. This endometrium thickness is used to predict the possibility of pregnancy in ART cycles. Estrogen and progesterone are the two main hormones responsible for morphological changes in the endometrial structure during the menstrual cycle. Estradiol promotes the expression of progesterone receptors, thus increasing the tissue sensitivity to progesterone. Today in Ukraine, oral and transdermal estrogens are widely used in ART programs. Transdermal estrogens are preferred due to their lack of a primary hepatic transit effect, which provides a higher safety profile compared to oral forms. A number of researches have been study the effectiveness of the Oestrogel®. It has been established that this drug is highly effective and safe for preparing patients for cryo-transfer of thawed embryos in ART programs. It has also been proven that the efficacy of estradiol transdermal gel in terms of pregnancy rate in patients treated in ART programs with gonadotropic releasing hormone antagonists is comparable to that of oral estradiol valerate and a transdermal patch. In another study, the frequency of miscarriages was significantly lower in patients treated with Oestrogel® compared with patients in the oral estradiol valerate group. Long-term pregnancy and live birth rates were also statistically significantly higher in the transdermal estradiol group. Conclusion. The estrogen drug Oestrogel® is an effective in improving the indicators of prolonged pregnancy and live birth. It can be effectively used for the treating "thin" endometrium and ART programs.